Happy Español: Development of 2D Mobile Learning Application for Spanish Language - Shee, Chen Yu; Ezak Fadzrin Bin Ahmad Shaubari (Applied Information Technology And Computer Science, 2025)
Happy Español is an innovative children’s mobile learning application designed to make learning Spanish. It is dedicated to helping Malaysian children learn Spanish in a fun and engaging way. The existing language learning applications focus less on children in Malaysia learning Spanish. The existing application also has a big selection of language making it harder for children to focus on one language. Therefore, this project proposes to develop a mobile learning application that helps children in Malaysia learn Spanish with supported language, English and Malay. The users targeted for this project are children aged 7 to 12. The Multimedia Mobile Content Development (MMCD) approach is used to develop the Happy Español application. The usability testing has resulted in an average score of 95.75 which is within the range of “Acceptable” in the Acceptability Ranges Score Scale, graded “A” on the Grade Scale, and rated “Excellent” based on the System Usability Scale (SUS). Therefore, it can be concluded that the Happy Español 2D mobile learning application is suitable for children aged between 7 to 12 years old to know and learn more about Spanish with enjoyment.